A Prediction Model Framework for Cyber-Attacks to Precision Agriculture Technologies. Issue 4 (2nd October 2018) - West, Jason
ABSTRACT: There are two types of precision agriculture systems - those that have been hacked, and those that will be. Connectivity and information flow represent the two key enabling factors for successful operation of the digital farm. These factors also represent the highest vulnerability to cyber-attack to disrupt food production. We introduce a principles-based framework to assess cyber-attack vulnerabilities in the technology itself as well as in the environment to which it is adapted. This provides the elements needed to construct a precision agriculture system protected from cyber-attacks and appropriately matched to the complexity level of the technology in the field.